2021
DOI: 10.1080/23248378.2021.1875065
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of track geometry degradation using artificial neural network: a case study

Abstract: The aim of this study has been to predict the track geometry degradation rate using artificial neural network. Tack geometry measurements, asset information, and maintenance history for five line sections from the Swedish railway network were collected, processed, and prepared to develop the ANN model. The information of track was taken into account and different features of track sections were considered as model input variables. In addition, Garson method was applied to explore the relative importance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…However, the authors in Lee et al [ 92 ] think the environmental factors are less important and consider the subgrade type and maintenance parameters (the number of compactions on ballast and initial TQI) instead. In the work of Khajehei et al [ 93 ], the authors used the Garson algorithm to calculate the relative importance of input variables, as shown in Table 5 , and found that the maintenance record, track degradation rate after tamping, and train load are more relevant to prediction accuracy than other variables.…”
Section: Prediction Methods Based On Machine Learningmentioning
confidence: 99%
“…However, the authors in Lee et al [ 92 ] think the environmental factors are less important and consider the subgrade type and maintenance parameters (the number of compactions on ballast and initial TQI) instead. In the work of Khajehei et al [ 93 ], the authors used the Garson algorithm to calculate the relative importance of input variables, as shown in Table 5 , and found that the maintenance record, track degradation rate after tamping, and train load are more relevant to prediction accuracy than other variables.…”
Section: Prediction Methods Based On Machine Learningmentioning
confidence: 99%
“…Additionally, the temporal frequency of our method is higher than theirs. Khajehei et al 16 used ANN to predict the degradation rate of SD LL . They fed a variety of exogenous data into the model.…”
Section: Related Workmentioning
confidence: 99%
“…Such freight cars include depressed-center flat cars, long-large flat cars, and well-hole cars. Exceptional heavy-duty railway freight cars exceeding the railway gauge in transport may endanger traffic safety on adjacent lines and even cause train derailment accidents [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Drones 2022, 6, x FOR PEER REVIEW 2 of 21 freight cars exceeding the railway gauge in transport may endanger traffic safety on adjacent lines and even cause train derailment accidents [2][3][4].…”
Section: Introductionmentioning
confidence: 99%